A model for determining student plagiarism: Electronic detection and academic judgement - Bretag, Tracey; Mahmud, Saadia (Journal of University Teaching and Learning Practice, 2009)
This paper provides insights based on the authors’ own practice as university instructors, researchers and arbitrators of student plagiarism. Recognising the difficulty in defining plagiarism while still acknowledging the practical importance of doing so, the authors find the common element between the various types of plagiarism to be the lack of appropriate attribution to the original source. The use of electronic text-matching software to detect different types of plagiarism is explored, and a model presented for identifying potential plagiarism in students’ work. The authors conclude that despite its shortcomings, electronic detection in combination with manual analysis, nuanced academic judgement and clear processes provide the means to determine if plagiarism has occurred.